1997
DOI: 10.1074/jbc.272.19.12650
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin G2 Is Up-regulated during Growth Inhibition and B Cell Antigen Receptor-mediated Cell Cycle Arrest

Abstract: (1996) J. Biol. Chem. 271, 6050 -6061). Cyclin G2 is highly expressed in the immune system where immunologic tolerance subjects self-reactive lymphocytes to negative selection and clonal deletion via apoptosis. Here we investigated the effect of growth inhibitory signals on cyclin G2 mRNA abundance in different maturation stage-specific murine B cell lines. Upon treatment of wild-type and p53 null B cell lines with the negative growth factor, transforming growth factor ␤1, or the growth inhibitory corticostero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
130
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(138 citation statements)
references
References 88 publications
6
130
0
Order By: Relevance
“…Several studies have shown that CCNG2 mRNA levels and/or protein levels are upregulated by growth inhibitory signals, including TGF-b (Horne et al, 1997) and downregulated by oncogenic pathways, such as PI3K-AKT in murine NIH 3T3 cells (Martinez-Gac et al, 2004), HER2, c-jun NH2-terminal kinase and the mammalian target of rapamycin/p70S6K (Le et al, 2007), and estrogen signaling (Stossi et al, 2006) in breast cancer cells. In immortalized ovarian surface epithelial and ovarian cancer cells, Nodal increased CCNG2 mRNA and protein levels, as well as CCNG2 protein stability (Xu et al, 2008).…”
Section: Nodal Induces Cyclin G2 Transcription Via Foxo3a G Fu and C mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that CCNG2 mRNA levels and/or protein levels are upregulated by growth inhibitory signals, including TGF-b (Horne et al, 1997) and downregulated by oncogenic pathways, such as PI3K-AKT in murine NIH 3T3 cells (Martinez-Gac et al, 2004), HER2, c-jun NH2-terminal kinase and the mammalian target of rapamycin/p70S6K (Le et al, 2007), and estrogen signaling (Stossi et al, 2006) in breast cancer cells. In immortalized ovarian surface epithelial and ovarian cancer cells, Nodal increased CCNG2 mRNA and protein levels, as well as CCNG2 protein stability (Xu et al, 2008).…”
Section: Nodal Induces Cyclin G2 Transcription Via Foxo3a G Fu and C mentioning
confidence: 99%
“…CCNG2 has a short half-life and it is quickly degraded through the ubiquitinproteasome pathway (Xu et al, 2008), providing a way by which arrested or quiescent cells may re-enter the cell cycle. Ectopic expression of the CCNG2 inhibited cell proliferation and induced cell cycle arrest in murine B cells (Horne et al, 1997), HEK293, Chinese hamster ovary cells (Bennin et al, 2002) and several cancer cell lines (Kim et al, 2004;Le et al, 2007;Xu et al, 2008). In breast cancer cells, CCNG2 expression is inhibited by HER2 through multiple intracellular pathways, including phosphoinositide 3-kinase (PI3K), c-jun NH2-terminal kinase and the mammalian target of rapamycin (Le et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ectopic cyclin G1 is primarily a nuclear protein, whereas tagged cyclin G2 is largely cytoplasmic [1,21,22]. Developmental expression and tissue distribution of cyclin G1 and G2 also differ [7,8,21]. In lymphocytes cyclin G1 expression is constitutive throughout the cell cycle, whereas cyclin G2 expression oscillates, peaking in late S and early G2 phase of the cell cycle [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the cyclin G1 gene [19,20], the cyclin G2 gene is not a transcriptional target of p53 [7][8][9]21]. Moreover, ectopic cyclin G1 is primarily a nuclear protein, whereas tagged cyclin G2 is largely cytoplasmic [1,21,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation